Vitamin D Enhances Efficacy of Oral Nifedipine in Treating Preeclampsia with Severe Features: A Double Blinded, Placebo-Controlled and Randomized Clinical Trial - Shi, Dan-Dan; Wang, Yong; Guo, Jun-Jun; Zhou, Ling; Wang, Na (Frontiers in Pharmacology, 2017)
Vitamin D (VD) has exhibited immunomodulatory role in the pathogenesis of preeclampsia. We hypothesize VD potentiate nifedipine treatment for preeclampsia by shortened the time to control blood pressure and prolong time before subsequent hypertensive crisis. We conduct a randomized trial of 683 primigravid women with preeclampsia, who were assigned to different treatment groups, either nifedipine+placebo or nifedipine+VD orally, by random after screening. Primary endpoints include time to control hypertension and time before another hypertensive crisis. Maternal adverse effects including nausea, vomiting, chest pain, mild headache, dizziness, maternal tachycardia, hypotension or shortness of breath, and neonatal parameters including birth weight and Apgar scores, as well as the minimum number of dosages needed to control hypertension were defined as secondary endpoints. Serum levels of cytokines tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) were also examined. There was a marked reduction of the time required to control hypertension and a significant lengthening (p=0.013) of the time before a new hypertensive crisis in participants received nifedipine+VD treatments (41.8±18.3 min), in comparison with the nifedipine+placebo controls (61.1±15.9 min). In women treated with nifedipine+VD, the minimum number of dosages needed to control hypertension was also lower. With regard to adverse effects, no statistical difference was observed between the two treatment groups. Moreover, treatment with VD increased IL-10 and reduced TNF-α serum levels. VD possesses the potential of serving as a safe and effective adjuvant to oral nifedipine in treating women with preeclampsia against hypertension, possibly through the upregulation of IL-10 and the downregulation of TNF-α.